Analisis Peran Guru dalam Pembelajaran Tatap Muka di Masa New Normal pada Siswa Kelas III di SDN Tajur 02 Kota Tangerang - Fauziah, Nur Sella; Awiria, Awiria; Taufiqurrahman, Asep (YASIN, 2022)
The purpose of this study was to determine the analysis of the teacher's role in the implementation of face-to-face learning during the new normal period in class 3A. This study uses a descriptive qualitative approach. The subject of this research is a class 3A teacher at SDN Tajur 02 Tangerang City. Data collection techniques using interviews, observation, and documentation. The data analysis technique uses data reduction, data presentation, and drawing conclusions. The results of this study indicate that the teacher's role in face-to-face learning during the new normal period in class 3A at SDN Tajur 02 is 1). as educators and teachers, namely teachers in ongoing learning have delivered material quite well, always involving students to be active in learning. 2). the teacher as a mediator/facilitator who tries to facilitate learning media that does not make students bored in participating in learning. 3). teachers as motivation, namely teachers always motivate students so that students are enthusiastic in participating in learning in the new normal period, 4). teacher as guide The teacher always guides students who have difficulty in learning and also who have difficulty in socializing.